Fighting Collusion by Permitting Price Discrimination - Magdalena Helfrich; Fabian Herweg (Center for Economic Studies and ifo Institute (CESifo), 2016)
We investigate the effect of a ban on third-degree price discrimination on the sustainability of collusion. We build a model with two firms that may be able to discriminate between two consumer groups. Two cases are analyzed: (i) Best-response symmetries so that profits in the static Nash equilibrium are higher if price discrimination is allowed. (ii) Best-response asymmetries so that profits in the static Nash equilibrium are lower if price discrimination is allowed. In both cases, firms' discount factor has to be higher in order to sustain collusion in grim-trigger strategies under price discrimination than under uniform pricing.
Keywords: D43; K21; L13; L41; 330; collusion; duopoly; grim-trigger strategies; third-degree price discrimination